도서지역 소형풍력발전기 에너지 발생량 평가 - 장춘만(Choon Man Jang); 이종성(Jong Sung Lee); 전완호(Wan Ho Jeon); 임태균(Tae Gyun Lim) (한국수소 및 신에너지학회 논문집, 2013)
This paper presents how to determine AEP(Annual Energy Production) by a small wind turbine in DuckjeokDo island. Evaluation of AEP is introduced to make a self-contained island including renewable energy sources of wind, solar, and tidal energy. To determine the AEP in DuckjeokDo island, a local wind data is analyzed using the annual wind data from Korea Institute of Energy Research firstly. After the wind data is separated in 12-direction, a mean wind speed at each direction is determined. And then, a small wind turbine power curve is selected by introducing the capacity of a small wind turbine and the energy production of the wind turbine according to each wind direction. Finally, total annual wind energy production for each small wind turbine can be evaluated using the local wind density and local energy production considering a mechanical energy loss. Throughout the analytic study, it is found that the AEP of DuckjeokDo island is about 2.02MWh/y and 3.47MWh/y per a 1kW small wind turbine installed at the altitude of 10 m and 21m, respectively.